EFEKTIVITAS KONSELING KELOMPOK SHAME ATTACKING EXERCISE BERDASARKAN Q.S ALI-IMRAN AYAT 139 UNTUK MENINGKATKAN KEPERCAYAAN DIRI SISWA DI SMK NEGERI 1 MOJOSONGO - Kasih, Lenie; Rozikan, Muhamad (IKIP Siliwangi, 2024)
This study aims to analyze the effectiveness of group counseling using the Shame Attacking Exercise technique based on Q.S Ali Imran verse 139 to help individuals overcome shame and improve students' self-confidence. The research method used is quantitative pre-experimental with a one-group pre-test and post-test design. The research participants consisted of 10 students with low self-confidence levels, selected through purposive sampling techniques. The instrument used was a self-confidence scale that had been tested for reliability. The results of the instrument consisted of 24 questions with a reliability value of 0.727. Data were analyzed using a T-Test. There was a significant difference in self-confidence scores before and after the treatment. The research results showed p = 0.000 (p < 0.05), indicating a positive effect on increasing students' self-confidence at SMK Negeri 1 Mojosongo. This study is expected to serve as a reference for school counselors in helping to improve students' self-confidence through group counseling using the Shame Attacking Exercise technique based on Q.S Ali Imran verse 139.